2021
DOI: 10.23925/2179-3565.2020v11i4p69-87
|View full text |Cite
|
Sign up to set email alerts
|

How Green Transformational Leadership Influences Sustainability? Mediating Effects of Green Creativity and Green Procurement

Abstract: Research on environment management in construction industry is as topic of debate globally. Thus, this study examined how green transformational leadership played for green building sustainability via green creativity and green procurement. We developed an assimilated research model to examine the impact of green transformational leadership, green creativity and green procurement on sustainability in construction industry by accessing resources-based view theory and componential theory of creativity. The sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…First, our results show that top management's GTL improves a firm's GOLC (GAC and GTC). This evidence is completely consistent with scientists arguing that there is a significant positive relationship between GTL and green creativity (Chen andChang, 2013a, 2013b;Mittal and Dhar, 2016;Jia et al, 2018;Bahzar, 2019;Zhang et al, 2020a;Shah et al, 2020;Mansoor et al, 2021;Jiang et al, 2021) and followers' green self-efficacy (Chen et al, 2014;Zafar et al, 2017;Zhang et al, 2020b;Farooq et al, 2021) and green mindfulness (Chen et al, 2015a(Chen et al, , 2015b. These findings also confirm the current literature claiming that TL improves AC (Ferreras M endez et al, 2017) and OL processes (Shin and Zhou, 2003).…”
Section: Research Findingssupporting
confidence: 89%
“…First, our results show that top management's GTL improves a firm's GOLC (GAC and GTC). This evidence is completely consistent with scientists arguing that there is a significant positive relationship between GTL and green creativity (Chen andChang, 2013a, 2013b;Mittal and Dhar, 2016;Jia et al, 2018;Bahzar, 2019;Zhang et al, 2020a;Shah et al, 2020;Mansoor et al, 2021;Jiang et al, 2021) and followers' green self-efficacy (Chen et al, 2014;Zafar et al, 2017;Zhang et al, 2020b;Farooq et al, 2021) and green mindfulness (Chen et al, 2015a(Chen et al, , 2015b. These findings also confirm the current literature claiming that TL improves AC (Ferreras M endez et al, 2017) and OL processes (Shin and Zhou, 2003).…”
Section: Research Findingssupporting
confidence: 89%
“…In the reviewed literature (Table 1) in the domain of green innovation, it is found that majority of researchers have indicated green product, green process and green service as main element of green innovation (Tang et al, 2018; Wang, Li, et al, 2020; Zhang, Zhao, et al, 2020) which is directly related to the operational activities of the organisation. Moreover, the other angle in the green innovation literature is support activities such as culture (Wang, Xue, et al, 2020; Yang et al, 2017), Institutional quality (Sun et al, 2019) Ambidextrous green innovation, Green Learning orientation and Green Knowledge acquisition (Wang, Xue, et al, 2020), Green Mindfulness (Shah et al, 2020), Green Self‐Efficacy (Zhang, Sun, et al, 2020) and governance such as green transformational leadership (Chen et al, 2014; Çop et al, 2021; Shah et al, 2020; Singh et al, 2020). Another author, Singh and El‐Kassar (2019) pointed out in his research that in this digitalisation world transformation process, the role of big‐data and green human resource management has a vital role in helping to achieve green innovation in the organisation for sustainable performance and organisational performance (El‐Kassar & Singh, 2019).…”
Section: Prior Literature and Framework Developmentmentioning
confidence: 99%
“…Team Performance Turkey; Poland (Shah, Jintian, Sukamani, & Kusi, 2022) To study the effect of agile leadership on career success.…”
Section: Operational Outcomementioning
confidence: 99%